SpaceOps 2002 Conference 2002
DOI: 10.2514/6.2002-t1-20
|View full text |Cite
|
Sign up to set email alerts
|

SCPS-TP, TCP and Rate-Based Protocol Evaluation For High Delay, Error Prone Links

Abstract: This paper describes testing performed to validate operation of Space Communications Protocol Suite Transport Protocol (SCPS-TP) relative to the specification and perform a comprehensive comparison of SCPS-TP protocol options to IP based protocols.Tests were performed at Glenn Research Center to validate the operation of SCPS-TP relative to the Consultative Committee on Space Data Systems (CCSDS) specification, to perform a comprehensive comparison of SCPS-TP protocol options to IP based protocols, and to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Indeed, previous studies (Sharafkandi and Malouch, 2005;Kawadia and Kumar, 2005) have demonstrated the poor TCP performances over wireless and multi-hop networks while other emphasize the good behaviour of rate-based congestion control over these networks (Chen et al, 2004;Anastasia and Passarella, 2003). In the context of satellite communications, several studies have also demonstrated the benefit of using ratebased congestion control protocols compared to TCP window-based variants and in particular in (Lawas-Grodek et al, 2002), the authors present performances comparison between SCPS-TP, TCP, TCP-Vegas and rate-based protocols which clearly show the strong benefit obtained by the latter in terms of throughput efficiency over long delay links.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies (Sharafkandi and Malouch, 2005;Kawadia and Kumar, 2005) have demonstrated the poor TCP performances over wireless and multi-hop networks while other emphasize the good behaviour of rate-based congestion control over these networks (Chen et al, 2004;Anastasia and Passarella, 2003). In the context of satellite communications, several studies have also demonstrated the benefit of using ratebased congestion control protocols compared to TCP window-based variants and in particular in (Lawas-Grodek et al, 2002), the authors present performances comparison between SCPS-TP, TCP, TCP-Vegas and rate-based protocols which clearly show the strong benefit obtained by the latter in terms of throughput efficiency over long delay links.…”
Section: Introductionmentioning
confidence: 99%